Indirect Effect of Hopelessness on Depression Symptoms Through Perceived Burdensomeness. Issue 5 (October 2019) - Nalipay, Ma. Jenina N.; Ku, Lisbeth
Hopelessness theory of depression posits that hopelessness due to negative inferences may serve as a proximal and sufficient cause of depression, while interpersonal theories suggest that interpersonal stress resulting from relationship problems and social rejection may lead to symptoms of depression. We propose that the two perspectives can be integrated by examining a model in which hopelessness predicts depression symptoms through two specific interpersonal stress constructs, thwarted belongingness and perceived burdensomeness, in a sample of university students from Macau ( N  = 350). Results of mediation analysis revealed a significant indirect effect of hopelessness on depression symptoms through perceived burdensomeness (indirect effect = .45; 95% confidence interval = .28 to .65), but not thwarted belongingness (indirect effect = .06; 95% confidence interval = −.05 to .18). Alternative models were also tested. When each interpersonal construct was treated as a separate mediator without controlling for the other, significant indirect effects of both perceived burdensomeness and thwarted belongingness were found. Moreover, when hopelessness was assigned as the mediator and interpersonal constructs as independent variables, significant indirect effects were likewise found for perceived burdensomeness and thwarted belongingness. Findings suggest that the two different yet compatible views about depression—hopelessness and interpersonal theories—may be integrated to provide a better understanding of the process of how depression symptoms occur. It also reinforces the importance of considering interpersonal factors in the study of depression, especially in societies where interpersonal relationships are highly valued.